2009
DOI: 10.1016/j.micres.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motility of the rhizobacterium Azospirillum brasilense in the presence of plant lectins

Abstract: The plant-beneficial bacterium Azospirillum brasilense can swim in liquids and swarm or migrate with the formation of microcolonies in soft media. To get closer to understanding the influence of natural environments on A. brasilense motility, we studied the individual and social movement of the bacterium in the presence of various plant lectins. The lectins with specificity for N-acetyl-beta-d-glucosamine oligomers (wheat germ, Solanum tuberosum and Ulex europeus agglutinins) decreased A. brasilense swimming s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Similar results have been obtained in intercropping experiments in which bacterial biomass and activity differed from those in mono-cropping systems (Latati et al, 2014;Li et al, 2009;Qiang et al, 2004;Song et al, 2006;Tang et al, 2014;Wang et al, 2007). Although more experiments are needed to identify the processes involved and the soil communities specifically targeted, the production and exudation of lectins by legumes has been shown to be capable of impacting Plant Growth-Promoting Rhizobacteria (PGPR) mobility, improving root colonization and the phytobeneficial activity of these PGPR (Schelud'ko et al, 2009). In the same way, the secretion of certain flavonoids, naringenin, for example, involved in the well-known symbiotic association between legumes and Rhizobium bacteria, could be responsible for Azospirillum brasilense Sp245 (PGPR) lateral root colonization (Jain and Gupta, 2003).…”
Section: Impact Of Intercropped Legumes On Beneficial Soil-borne Bactsupporting
confidence: 65%
“…Similar results have been obtained in intercropping experiments in which bacterial biomass and activity differed from those in mono-cropping systems (Latati et al, 2014;Li et al, 2009;Qiang et al, 2004;Song et al, 2006;Tang et al, 2014;Wang et al, 2007). Although more experiments are needed to identify the processes involved and the soil communities specifically targeted, the production and exudation of lectins by legumes has been shown to be capable of impacting Plant Growth-Promoting Rhizobacteria (PGPR) mobility, improving root colonization and the phytobeneficial activity of these PGPR (Schelud'ko et al, 2009). In the same way, the secretion of certain flavonoids, naringenin, for example, involved in the well-known symbiotic association between legumes and Rhizobium bacteria, could be responsible for Azospirillum brasilense Sp245 (PGPR) lateral root colonization (Jain and Gupta, 2003).…”
Section: Impact Of Intercropped Legumes On Beneficial Soil-borne Bactsupporting
confidence: 65%
“…Several theories have been proposed to explain the effect of legume intercropping on the structure of rhizobacterial communities. It has been demonstrated that legume secretion such as flavonoids, have the ability to influence plant growth-promoting rhizobacteria (PGPR) mobility, improving root colonization and phytobeneficial activity of these PGPR, leading to plant facilitation [14,15]. Another example is that N-acyl homoserine lactone (N-AHL) in several legume root exudates affects gene expression in quorum sensing, a bacterial regulation process [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…and spontaneous and induced changes in the genome, in particular, in the structure of megaplasmids, have a great influence on the social behavior of the bacteria. The genome changes are accompanied by phenotypic variations in the social motility of azospirilla (swarming → accelerated swarming; swarming → spreading with the formation of microcolonies; spreading with the formation of microcolonies → accelerated swarming), and they can lead to changes in the formation of biofilms and in the early stages of plant-root colonization (Katsy, Prilipov, 2009;Schelud'ko et al, 2009). Insertion elements responsible for the plasticity of A. brasilense megaplasmids were described for the first time.…”
Section: The Key Results Obtained At the Ibppm Ras In Studies Of Azospirillum Bacteria As Model Objectsmentioning
confidence: 99%